2008
DOI: 10.1097/01.hmr.0000324910.26896.91
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing networks related to hospital quality measurement and reporting

Abstract: This study finds that good-coding performance is systematically associated with a knowledge sharing network structure rich in brokerage and hierarchy (with leaders connecting different professional subgroups to each other and to the external environment) rather than in density (where everyone is directly connected to everyone else). From a health care management perspective, this study suggests that to improve hospital coding performance, senior administrators must undertake proactive and unceasing efforts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
67
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 5 publications
0
67
0
1
Order By: Relevance
“…While earlier research has suggested that peer-to-peer dense communication networks may be most effective for tacit knowledge exchange [39,40] , this literature was restricted to business corporations. Applying the framework to the healthcare organizational context has suggested that proactive and periodic top-down communications may be effective for tacit knowledge exchange, collective learning, and change [31][32][33] . The reasoning is that professional organizations contain multiple professional subgroups that differ in shared expertise and value systems.…”
Section: Literature On Organizational Change Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…While earlier research has suggested that peer-to-peer dense communication networks may be most effective for tacit knowledge exchange [39,40] , this literature was restricted to business corporations. Applying the framework to the healthcare organizational context has suggested that proactive and periodic top-down communications may be effective for tacit knowledge exchange, collective learning, and change [31][32][33] . The reasoning is that professional organizations contain multiple professional subgroups that differ in shared expertise and value systems.…”
Section: Literature On Organizational Change Implementationmentioning
confidence: 99%
“…Research on implementing & sustaining organizational change, emanates from the literature on "Professional Complex Systems," which provides a broader framework for addressing the problem of interest [31][32][33][34][35][36][37][38] . Complex systems theory has repeatedly emphasized that collective learning is an essential pre-requisite to organizational change; and the collective learning in turn, requires the creation of collective tacit knowledge [35,36] , or knowledge embedded in practice (and not easily communicable).…”
Section: Literature On Organizational Change Implementationmentioning
confidence: 99%
“…A key limitation of the TIP literature however, is that while it helps understand causes of unintended consequences of technology implementation, it does not by itself provide solutions to overcome them. A more recent stream of literature on knowledge-in-practice (KIP), which emanates from the broader literature stream on implementing and sustaining change in healthcare organizations has sought to understand how the creation of new communication (network) structures (or social structures) could enable the creation of new knowledge to in turn facilitate collective learning and organizational change [19][20][21][22][23][24][25][26][27] .…”
Section: Understanding and Detecting The Causes Of Unintended Adversementioning
confidence: 99%
“…국외에서는 간호사들의 지식공유가 간호사의 임상수행능력, 환 자안전, 환자 만족도에 실질적으로 영향을 미치는 것으로 확인되었 으며 [6], 이에 따라 조직차원에서 간호사가 속한 부서 및 조직에서의 지식공유를 위한 방안을 단계적으로 확대하고 있다 [7]. 이를 위하여 기존 정보시스템을 인트라넷으로 구축하고 블로그, wikis, podcasts 등과 같은 다양한 도구를 통하여 사용자들이 실질적으로 지식을 창출하고 공유할 수 있는 환경을 조성하였다 [8].…”
unclassified